Evaluation of the Surveillance System in Kiryandongo Refugee Settlement, Kiryandongo District, Uganda, April 2017 - Denis Nixon Opio; Paul Edward Okello; Lilian Bulag; Daniel Kadobera; Benon Kwesiga; Innocent Nkonwa; Alex Riolexus Ario (Journal of Interventional Epidemiology and Public Health)
Introduction: Integrated Disease Surveillance and Response (IDSR) involves surveillance of priority diseases and conditions, and is implemented in many African countries, including Uganda. During humanitarian emergencies, public health surveillance systems such as IDSR may face challenges. We assessed the capacity of health facilities (HF) in Kiryandongo District, a district with a large and recent refugee influx, to perform IDSR core functions.